A Comparison of Physical Therapy Modalities Versus Acupuncture in the Treatment of Fibromyalgia Syndrome: A Pilot Study - Ozen, Selin; Saracgil Cosar, Sacide Nur; Cabioglu, Mehmet Tugrul; Cetin, Nuri (The journal of alternative and complementary medicine (New York, N.Y.), 2019)
Physical therapy (PT) modalities are used in the treatment of fibromyalgia syndrome (FMS). Acupuncture is a treatment option often sought after by FMS patients. The aim of this study was to compare the effects of PT modalities with those of acupuncture on pain, daily function, and quality of life in FMS patients. A comparative effectiveness study. Forty-four female patients between the ages of 18-70 years presenting to Baskent University Faculty of Medicine Department of Physical and Rehabilitation Medicine with a new diagnosis of FMS according to the American College of Rheumatology, with manifestations of chronic widespread musculoskeletal pain symptoms, normal routine blood tests, and a desire to receive PT or acupuncture were included in the study. Exclusion criteria included the presence of neurologic, inflammatory, endocrinologic, and other chronic diseases, psychiatric illness, use of antidepressants or analgesics, and contraindication to treatment with PT modalities. One group (n = 22) received 15 sessions of hotpack, transcutaneous electrical nerve stimulation (TENS), and ultrasound to the tender points of the cervical and upper back regions. The other group (n = 22) received 10 sessions of formulated acupuncture aimed at treating pain of the neck, upper, and lower back regions. Pain, functionality, and quality of life measured using the Short Form McGill Pain Questionnaire (SF-MPQ) and Fibromyalgia Impact Questionnaire (FIQ) before and after treatment. There was a reduction in all SF-MPQ domains and FIQ scores after treatment in both the PT and acupuncture groups. There was no difference in pre- and post-treatment scores between the two groups. PT modalities and acupuncture can be effectively used in the treatment of FMS. Even though one treatment option was not found to be more beneficial than the other, longer post-treatment follow-up may help determine the superior treatment option.